Utilization of Malunggay (Moringa oleifera) seeds in the production of Malunggay energy bar - Borreros, Joseph Cruz.
Nutrition and energy bars are gaining popularity nowadays because of our active and fast paced lifestyle. Hence, this study aimed to incorporate malunggay (Moringa oleifera) seeds in an energy bar is dubbed as a "natural nutrition for the tro6% cpics". Three formulations of malunggay seed-oatmeal ratio, specifically, 10:90, 20:80, and 30:70 were explored in this study. Based on the Preference Ranking Test, the formulation with 20:80 malunggay seed-oatmeal ratio was most preferred and therefore further subjected to Acceptability Test using 9-point Hedonic Scale. Acceptability test and Sign Test revealed that the formulation with 20:80 malunggay seed-oatmeal ration has acceptable appearance, flavour, texture, aftertaste, and overall attributes. Proximate analysis showed that the product has 5.65% moisture content, 1.41% crude ash, 18.01% crude fat, 1.9rude fiber, 12.94% crude protein, and 60.03% carbohydrates content. Furthermore, based on its moisture content, it is considered as low moisture food with 1-2 years shelf-life under proper packaging material. The total fat, carbohydrates, and protein content of the final product were compared to the original recipe of the energy bar and the results showed 0.44-0.80% difference in values.
Thesis, Undergraduate (B.S. Food Technology)-U.P. Mindanao
Keywords: Malunggay; Moringa oleifera; Acceptability Test; Preference Ranking Test; Proximate analysis; Energy bar; Malunggay seeds; Malunggay energy bar; 9-point Hedonic Scale; Natural nutrition for the tropics; Seed-oatmeal ratio